Influence of Oecophylla longinoda latreille, 1802 (Hymenoptera: Formicidae) on mango infestation by Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) in relation to Senegalese orchard design and management practices - Diame, L.; Grechi, I.; Rey, J.; Sane, C.A.; Diatta, P.; Vayssières, Jean-François; Yasmine, A.; Bon, H. de; Diarra, K. (Entomological Society of Southern Africa, 2015)
Damage caused by the fruit fly Bactrocera dorsalis (Hendel) (syn. B. invadens Drew, Tsuruta & White) (Diptera: Tephritidae) on mangoes in Senegal leads to production losses. A potential biological control agent against this pest is the weaver ant Oecophylla longinoda Latreille (Hymenoptera: Formicidae). Senegalese mango-based orchards present a diversity in design and management practices that can influence the abundance of these two species in orchards. In this study we evaluated i) the ability of the O. longinoda ant to limit B. dorsalis damage in Senegalese orchards, and ii) variations in population abundance for these two species depending on orchard design and management practices. The study was conducted in Senegal in the Niayes area and the Thiès plateau. Fifteen orchards were sampled among three out of four kinds of orchards identified in this area: (1) ‘No-input mango diversified orchards’, (3) ‘Medium-input citrus-predominant orchards’ and (4) ‘Medium-input large mango- or citrus-predominant orchards’. In one of the orchards we measured infestation rates and numbers of fly pupae that developed from mangoes collected from trees (cv. Kent) ‘with’ and ‘without’ O. longinoda colonies over three harvesting periods (May, July and August) in 2013. The abundance of O. longinoda and B. dorsalis was measured for two months in the dry season and two others in the rainy season in the 15 orchards in 2012. The presence of O. longinoda on trees reduced the proportion of mangoes attacked by B. dorsalis as well as the number of pupae that developed from infested mangoes. The abundance of O. longinoda and B. dorsalis was negatively correlated. The abundance varied depending on the orchard design and management practices. O. longinoda abundance was greater in orchard types 1 and 3 than in type 4. Conversely, B. dorsalis abundance in the rainy season tended to be greater in orchard type 4 than in types 1 and 3. This study showed that O. longinoda is effective in limiting mango infestations by B. dorsalis. It also showed that the abundance of these two species was influenced by the orchard design and management practices. Therefore, using O. longinoda to control fruit flies is possible in Senegalese mango-based orchards by promoting weaver ant preservation.